Algorithm for Searching Inhomogeneities in Inverse Nonlinear Diﬀraction Problems - A. O. Lapich; M. Y. Medvedik (Учёные записки Казанского университета: Серия Физико-математические науки)
This study aims to solve the inverse problem for determining the heterogeneity of an object. The scattered ﬁeld was measured outside its boundaries at a set of observation points. Both the radiation source and observation points were assumed to be located outside the object. The scattered ﬁeld was modeled by solving the direct problem. The inverse problem was solved using a two-step method. Nonlinearities of various types were considered. When introducing the computational grid, the generalized grid method was applied. A numerical method for solving the problem was proposed and implemented. The numerical results obtained illustrate how the problem is solved for speciﬁed experimental data.